Maximizing the disinfection effectiveness of 254 nm UV-C light with a special design unit: simulation and experimental approaches - Chen, Hanyu; Moraru, Carmen I.; Protasenko, Vladimir V. (Frontiers in Food Science and Technology, 2023)
We propose a special design enclosure device that promotes isotropic distribution of germicidal UV-C light for the effective disinfection of difficult to reach surfaces. We used experimental and computational approaches to investigate the disinfection efficacy of this device against Escherichia coli and Listeria innocua. Stainless steel, Copper metal, and a Copper polymer were used as solid substrates of varying roughness and hydrophobicity. Bacteria reductions of up to 6.9 log CFU were achieved at various locations relative to the UV-C source after 3 min of treatment (20–990 mJ/cm2 cumulative fluence depending on the location). Inactivation kinetics was nonlinear and followed the Weibull model (0.77 ≤ R2 ≤ 0.97). Optical ray tracing simulation was used to generate maps of spatial light distribution, which were then coupled with microbial inactivation kinetics to create spatial maps of inactivation. The modeling approach used accurately predicted microbial inactivation at various locations, with only small discrepancies (±8%) between predicted and experimental data. These findings demonstrate that the proposed device is suitable for disinfecting various hard to reach surfaces, with numerous possible applications in the food and healthcare industries. Additionally, the modeling approach used here can be used to aid in the design of a highly effective Ultraviolet treatment system.